PSYCHOPHYSIOLOGICAL PARAMETERS OF MILITARY LEADERSHIP - Пампуха, Ігор; Лоза, Віталій; Сіроштан, Олексій; Собіщанський, Сергій; Філімонова, Наталя (Київський національний університет імені Тараса Шевченка, 2025)
B a c k g r o u n d . Leadership is examined through various theoretical frameworks, including perspectives that view it as a product of innate personality traits as well as characteristics acquired through training and experience. However, the role of psychophysiological parameters in underpinning leadership qualities in military personnel remains a topic of debate. This article focuses on the investigation of military leadership through the lens of individual psychophysiological traits or characteristics observed in military personnel. M e t h o d s . The study employed methods of analysis, comparison, synthesis, generalisation, and systematisation of domestic and international research on the concept of leadership, features of military leaders, methods for identifying leadership traits, and psychological and psychophysiological parameters in military personnel relevant to leadership development. R e s u l t s . A comprehensive analysis of the concept of leadership in the military context was conducted. A three-level structure of core factors involved in the development of a military leader is proposed. This structure is based on the innate psychophysiological characteristics of the human central nervous system, which determine the potential for developing leadership qualities. The second level concerns the acquisition of military leadership competencies and attributes during training, where innate traits influence the manifestation of specific leadership behaviours. The third level represents environmental factors within the military setting that may promote the development of leadership potential. Based on the conducted analysis, the following psychophysiological characteristics are proposed as key indicators of military leadership: nervous system strength, functional mobility of neural processes, short-term visual and verbal working memory, associative memory capacity, and resistance to information overload. C o n c l u s i o n s . Alongside other individual and educational characteristics, the proposed psychophysiological parameters should be regarded as part of the psychophysiological profile of a tactical-level military leader. Given that these parameters are objective indicators, further experimental focus is recommended on their in-depth study.

В с т у п . Лідерство розглядається в межах різних теорій, як із погляду вроджених індивідуальних характеристик рис людини, так і властивостей, набутих нею внаслідок навчання і досвіду. Водночас дискусійним залишається питання психофізіологічних параметрів, які можуть бути в основі виявів лідерських якостей військовослужбовців. Статтю присвячено дослідженню військового лідерства з погляду індивідуальних психофізіологічних властивостей або характеристик у військовослужбовців. М е т о д и . У дослідженні використано методи аналізу, порівняння, синтезу, узагальнення, систематизації досліджень закордонних і вітчизняних учених щодо поняття лідерства, особливостей військових лідерів, методів визначення наявності лідерських якостей та психологічних і психофізіологічних параметрів військовослужбовців, необхідних для формування лідера. Р е з у л ь т а т и . Проведено комплексний аналіз поняття лідерства у військовій сфері. Запропоновано трирівневу структуру основних чинників становлення військового лідера. В основу трирівневої структури покладено властивості вроджених психофізіологічних особливостей центральної нервової системи людини, які визначають її можливості до розвитку лідерських якостей. Другий рівень характеризується набуттям військовослужбовцем атрибутів і компетенцій військового лідера під час навчання, де вроджені психофізіологічні характеристики обумовлюють вияви тих чи інших лідерських якостей. Третій рівень відображає чинники військового середовища, які можуть сприяти розвитку лідерських якостей військовослужбовця. За результатами проведеного аналізу основними психофізіологічними характеристиками лідерства у військових фахівців пропонується визначати силу нервової системи, функціональну рухливість нервових процесів, стан візуальної та вербальної оперативної пам'яті, асоціативної пам'яті, а також здатність протистояти інформаційному перевантаженню. В и с н о в к и . Поряд з іншими індивідуальними й освітніми характеристиками запропоновано психофізіологічні параметри як частину психофізіологічного портрета військового лідера тактичної ланки. Зважаючи на те, що психофізіологічні параметри є об'єктивними показниками, вважаємо доречним зосередити експериментальний фокус на подальшому їх вивченні.
ПСИХОФІЗІОЛОГІЧНІ ПАРАМЕТРИ ВІЙСЬКОВОГО ЛІДЕРСТВА
Keywords: лідерство; військове лідерство; сила нервової системи; асоціативна пам'ять; оперативна пам'ять; інформаційне перевантаження; психологія; leadership; military leadership; nervous system strength; associative memory; working memory; information overload